Determinación de zonas de desove mediante un estudio de ictioplancton en la cuenca media del río Nanay - Pezo Bendayan, Adriano (2023)
During the months of March to August 2019, the study was carried out to identify the spawning areas in the middle basin of the Nanay River by relating the embryonic development of fish eggs and the speed of the river current, the sampling they were done fortnightly and three times both in the rising and emptying season, in the superficial layer and center of the river, then the state of embryonic development and the time required according to the reports generated36 were analyzed. The results indicate that during the entire There is reproduction every year, but it is more intense during the flood season. The hydrographic system of the Allpahuayo-Mishana National Reserve and the middle basin of the Nanay River still conserve the arboreal and shrubby plant formations, despite the impact that is produced in their environment. It has been determined that spawning takes place in the section from Loboyacu to the Porvenir creek. There is no doubt that complementary and permanent studies on ichthyoplankton are still needed to allow us to develop a spawning area protection plan for the entire Nanay River basin in order to conserve the fish resources of this part of the Peruvian Amazon. Of conserving the ictical resources of this part of the Peruvian Amazon.